Comparação do uso do endoscópio e do espelho no exame da cavidade oral em equinos mangalarga marchador - Mansur, Victor Ferreira Ribeiro (2022)
The present study aimed to evaluate the use of oral endoscopy as a method of diagnosing cheek teeth disorders in Mangalarga Marchador horses, compared to the conventional method, in addition to establishing the prevalence of oral disorders in this population and the influence of age and location of the teeth. injuries on their occurrence. To carry out the study, 100 horses, between 2 and 18 years old, from three farms in Três Corações (MG) were used. The examination of the oral cavity was performed using two different examination techniques, conventional clinical examination, with a dental mirror, and endoscopic examination, with a rigid endoscope. The dental mirrors had a circular shape of 3 and 5 cm in diameter. The rigid endoscope had a high definition camera inserted at 90°. All animals were submitted to both evaluations, each technique being performed by qualified and trained veterinarians, independently and without prior knowledge among the evaluators. When comparing the two diagnostic methods, in terms of frequency of occurrence of lesions in the total number of teeth/soft tissues evaluated, it was possible to observe a significant difference between the methods (<0.001). Thus, oral endoscopy was able to diagnose a greater number of lesions (2631) than the conventional exam (2552). Considering each type of lesion, there was a significant difference between the diagnostic methods for diastema, infundibular caries and peripheral caries. For all these conditions, the endoscopic examination was able to identify a greater number of lesions. All animals had at least one lesion identified by conventional examination or by endoscopic examination. Excessive enamel tips (PEED) was the most prevalent lesion (96%), followed by ulcers (38%), ramps (36%), infundibular caries (28%) and peripheral caries (22%). The other conditions showed a frequency lower than 10%. When considering the conditions individually, a significant correlation (p<0.001) was observed between age and prevalence of PEED, step, wave, periodontitis, infundibular caries and peripheral caries and deciduous tooth retention. When analyzing the location of the lesion as a risk factor for the occurrence of conditions, significant differences (p<0.001) were observed for the prevalence of infundibular caries, peripheral caries and ramps. The present study can conclude that the endoscope examination improves the visual examination of the oral cavity. The prevalence of dental/oral disorders in the population evaluated is considerably high, mainly associated with the presence of PEED, ulcers and caries.